CONVERGENCE DISCUSSIONS FOR THE FORMATION OF POLICY REGULATIONS IN LOCAL LAWS - Ade Arif Firmansyah; Malicia Evendia (Universitas Syiah Kuala, 2022)
Policy regulations are needed in the administration of government. As the rule of law country, Indonesia has a consequence of acting based on law. But the summary of the regulation of the formation of policy regulations raises various multi-interpretations in its implementation. This raises problems, including the substance of the material that exists in the policy regulations is contrary to the laws and regulations. This study aims to find the concept of convergence of the formation of policy regulations in local laws. This is doctrinal legal research examining various laws and regulations. The research shows that there is a discourse on the convergence of the formation of policy regulations as part of regional legal provisions in an effort to protect preventive law hence officials of local government in the formation of policy regulations follow rules and guidelines that have been worded in legislations. The convergence of the formation of policy regulations at the regional level is carried out by changing the Regulation of the Minister of Home Affairs Number 80 of 2015 in connection to the Regulation of the Minister of Home Affairs Number 120 of 2018 concerning the Establishment of Regional Laws hence the laws in the form of regulations consist of regulations, Regional Representative Houses’ regulations, and regional policy regulations.